Pemurnian diasilgliserol dari produk gliserolisis minyak sawit mentah dengan kromatografi kolom Purification of diacylglycerol from glycerolysis products of crude palm oil using column chromatography - . TRI-PANJI; . SUHARYANTO; Urip PERWITASAR (INDONESIAN RESEARCH INSTITUTE FOR BIOTECHNOLOGY AND BIOINDUSTRY, 2011)
AbstractVegetable oil enriched with diacylglycerol (DAG) isknown as healthy oil. This oil is much more expensive thancooking oil. Production of DAG could be performed byglycerolysis process of CPO using specific lipase of 1,3-glyceride from Rhizopus oryzae mold. Product derived fromglycerolysis process of CPO is a mixture of DAG, mono-acylglycerol (MAG), free fatty acid (FFA) and residual ofunglycerolysed triacylglyserol (TAG). Therefore the DAGproduct has to be isolated from other components in order toget high purity of DAG. The objective of the research was topurify and to find out optimal concentration of DAG derivedfrom a mixture product of CPO glycerolysis at laboratoryscale experiment (total reactant for glycerolysis was93.8 mL) and semipilot scale experiment (10 times oflaboratory scale) using column chromatography with silicagel as stationary phase. The research showed that thehighest DAG content could be collected at fraction of 26 th i.e65%, while at semipilot scale experiment the highest contentof DAG (97%) was achieved at 64 to 66th fraction.Reglycerolysis of residual CPO only yielded 8.24%glycerolysis product which was much lower than that of thefirst glycerolysis reaching 46.67%. The highest DAG derivedfrom the second reglycerolysis product was achieved at 24 thfraction reaching 35.71 % .AbstrakMinyak nabati kaya kandungan diasilgliserol (DAG)dikenal sebagai minyak sehat (healthy oil). Minyak ini jauhlebih mahal dari minyak makan biasa. Produksi DAG dapatdilakukan dengan proses gliserolisis CPO menggunakanenzim lipase spesifik 1,3-gliserida dari kapang Rhizopusoryzae. Produk gliserolisis CPO triasilgliserol adalahcampuran DAG, monoasilgliserol (MAG) dan asam lemakbebas (ALB) serta residu triasilgliserol (TAG) yang tidaktergliserolisis. Oleh karena itu DAG yang terbentuk harusdipisahkan dari komponen lainnya agar diperoleh fraksi DAGdengan kemurnian tinggi. Penelitian ini bertujuan untukmemurnikan dan menetapkan konsentrasi DAG yang dapatdiperoleh dari gliserolisis CPO skala lab (total reaktan93,8 mL) dan skala semipilot (10 kali skala laboratorium)dengan kromatografi kolom menggunakan fase padat silikagel. Residu TAG dari gliserolisis pertama digunakan untukgliserolisis kedua atau gliserolisis ulang. Hasil penelitianmenunjukkan bahwa fraksi DAG dengan konsentrasitertinggi diperoleh pada fraksi ke-26 yaitu sebesar 65%,sedangkan pada percobaan dengan skala semipilot (10 kaliskala laboratorium) diketahui bahwa konsentrasi DAGtertinggi (97%) diperoleh pada fraksi ke-64 sampai denganke-66. Gliserolisis kedua dari residu CPO hanya mampumenghidrolisis TAG menjadi campuran DAG, MAG danALB sekitar 8,24%, lebih kecil dari reaksi gliserolisispertama yaitu sebesar 46,67%. DAG tertinggi yang berhasildikumpulkan dari produk gliserolisis kedua adalah padafraksi ke-24 yaitu sebesar 35,71% .